Endocrine Flawed In COVID-19 Era - Akter, Farhana; Ahmad, Rahnuma; Haque, Mainul (Bangladesh Journal of Medical Science, 2021)
The clinical practice and social relationships have been changed since the emergence of COVID-19. It is declared a global pandemic affecting millions of people across the world. SARS-CoV-2 virus while infecting human has been noted to affect several vital organs and biological systems. This can occur directly through virus-induced damage or indirectly due to the host response after virus entry, which produce a negative impact on body systems. Human endocrine system similar fatal effect. Thereafter, the knowledge and clinical expertise about the management of the endocrine pathological consequences of COVID-19 is essential in the current pandemic situation. The need of such clinical proficiency is increasing more demanding as SARS-CoV-2 pandemic is growing towards more devastating phase. The coronavirus enters the human body by using the angiotensin converting enzyme 2 (ACE-2). Other than the pneumocytes, ACE-2 is expressed by several endocrine glands like the pancreas, pituitary gland, adrenal glands, thyroid, ovary, and testes. Diabetes has a significant impact on covid 19. Diabetes Mellitus is one of the comorbidities most frequently linked to severity and mortality resulting from COVID-19 infection. Thus, careful management that includes modification of treatment may be needed to protect from the most dangerous outcomes of the virus infection or hospitalization with COVID-19, not only for patients with a known history of diabetes but also those suffering SARS-CoV-2 induced new-onset diabetes. Those suffering from obesity are more susceptible to SARS-CoV-2 as well as to adverse effects. In order to limit the susceptibility and severity of SARS-CoV-2 infection, there needs to be adequate management of nutrition of obese and undernourished patients. Hypothalamic-pituitary axis suppression, adrenal insufficiency, thyroid dysfunction, hypocalcemia, vitamin D lack, and vertebral fractures have also been reported as frequent findings in COVID-19 infected individuals who needed to be hospitalized and often associated with fatal clinical outcomes. Prompt glucocorticoid adjustment is also required in patients with COVID-19 having adrenal insufficiency. Addressing hormonal status may limit further treatment burden for a COVID-19 infected patient. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.49-64